2001
DOI: 10.1007/bf02850301
|View full text |Cite
|
Sign up to set email alerts
|

A new tool for predicting erectile dysfunction

Abstract: The Sexual Health Inventory for Men (SHIM) is an effective way to assess erectile difficulty (ED). Despite documented efficacy, however, many physicians may be reluctant to incorporate it into clinical practice because of the intimate nature of the questionnaire. In an attempt to devise and test an easy-to-use computer-based SHIM score indicator for office use, more than 30,000 SHIM questionnaires were administered to men visiting physicians' offices in 2000. Information about age, current smoking status, diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
0
17
0
1
Order By: Relevance
“…55 In a recent analysis of more than 30 000 SHIM questionnaires administered in over 600 physicians' offices, the predicted relationship between ED, age and other medical risk factors (hypertension, diabetes, ischemic heart disease) was observed. 56 Additionally, this study reported a high sensitivity (81.8%) and moderate specificity (57.7%) for detection of ED in patients scoring below 21 on the test. Based on these findings, the authors concluded that the SHIM provides a convenient method for rapidly identifying patients …”
Section: Brief Screening Versionmentioning
confidence: 60%
“…55 In a recent analysis of more than 30 000 SHIM questionnaires administered in over 600 physicians' offices, the predicted relationship between ED, age and other medical risk factors (hypertension, diabetes, ischemic heart disease) was observed. 56 Additionally, this study reported a high sensitivity (81.8%) and moderate specificity (57.7%) for detection of ED in patients scoring below 21 on the test. Based on these findings, the authors concluded that the SHIM provides a convenient method for rapidly identifying patients …”
Section: Brief Screening Versionmentioning
confidence: 60%
“…Recently, the International Index of Erectile Function (IIEF), the Brief Male Sexual Function Inventory (BMSFI), the Sexual Health Inventory for Men (SHIM), the Cologne Erectile Inventory (KEED) and also one question scales were created. [10][11][12][13][14][15][16][17][18][19][20] The IIEF is a commonly used validated questionnaire, but is not related to the WHO definition. Since many prevalence studies used various questionnaires, comparison between prevalence estimates of ED remains unavailable and therefore standardisation in the assessment of ED (definition) and presentation of prevalence estimates (overall and age-specific) and relations with risk factors has been recommended to facilitate comparison of results across studies.…”
Section: Introductionmentioning
confidence: 99%
“…10 Offering the sexual questionnaire in a computerized form has several worthy advantages. It offers privacy, as each examinee sits in front of a touch screen in a station, separated from the others.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] It is a convenient and reliable tool to identify rapidly patients with ED who should be further assessed. 10 There is high correlation and agreement between SHIM and patient self-assessment of ED, validating SHIM for use in the classification of ED severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation